Photodegradation of benzene, toluene, p-xylene in aqueous phase using zno, tio2, sno2, wo3 and fe2o3 photocatalysts prepared via sol-gel method / Zul Adlan Mohd Hir and Rusmidah Ali - Mohd Hir, Zul Adlan; Ali, Rusmidah (Universiti Teknologi MARA Cawangan Pahang, 2021)
Aromatic volatile organic compounds (VOCs) such as benzene, toluene and p-xylene (BTX) have been long considered as carcinogenic and toxic to humans as well as environmentally harmful. The continuous exposure to these compounds could cause neurasthenia and even leukemia. Therefore, necessary actions should be taken to combat the presence of these compounds in water. In this work, the photodegradation of BTX mixture was carried out using five different types of semiconductor oxides prepared via sol-gel method, namely ZnO, TiO2, SnO2, WO3 and Fe2O3 with UV-light centered at 365 nm. The band gap energy for all prepared photocatalysts was estimated from Kubelka-Munk function. The suitability of the band gap of ZnO (3.20 eV) and TiO2 (3.00 eV) envisages the best degradation performances at 0.10 g loading for both photocatalysts, by degrading ~42% BTX mixture in original condition. Such photoactivity is mainly ascribed to photons energy absorption and efficient separation of photoinduced electron–hole pairs derived from the photocatalysts. This further promotes the formation of reactive radicals’ species which responsible for the bond-breaking of the VOCs.